2013
DOI: 10.1007/s11099-013-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesophyll conductance variations in response to diurnal environmental factors in Myrcia paivae and Minquartia guianensis in Central Amazonia

Abstract: Mesophyll conductance (g m ) is essential to determine accurate physiological parameters used to model photosynthesis in forest ecosystems. This study aimed to determine the effects of time of day on photosynthetic parameters, and to assess the effect of using either intercellular CO 2 concentration (C i ) or chloroplast CO 2 concentration (C c ), on maximum carboxylation velocity of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), V cmax . We used Amazonian saplings of Myrcia paivae and Minquartia g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
2
15
0
3
Order By: Relevance
“…PPF and air temperature values recorded in this study are similar to those reported previously for the same region (Nascimento and Marenco, 2013). Shuttleworth et al (1984) also found that radiation above the canopy is only 40 % of extra-terrestrial radiation, about Leaf traits and sapling growth Although there was variation in soil water content and  leaf across rainfall season, neither sapling growth rates nor the leaf traits (photosynthetic parameters, LT, SLA, and the relative chlorophyll content) were affected by rainfall seasonality (p > 0.05).…”
Section: Physical Environmentsupporting
confidence: 91%
See 1 more Smart Citation
“…PPF and air temperature values recorded in this study are similar to those reported previously for the same region (Nascimento and Marenco, 2013). Shuttleworth et al (1984) also found that radiation above the canopy is only 40 % of extra-terrestrial radiation, about Leaf traits and sapling growth Although there was variation in soil water content and  leaf across rainfall season, neither sapling growth rates nor the leaf traits (photosynthetic parameters, LT, SLA, and the relative chlorophyll content) were affected by rainfall seasonality (p > 0.05).…”
Section: Physical Environmentsupporting
confidence: 91%
“…V cmax and J max data were standardized to 25 ºC (Nascimento and Marenco, 2013). V cmax and J max were obtained after measuring photosynthesis at CO 2 concentrations of 50 to 2000 µmol mol −1 and saturating light intensity (1000 µmol m −2 s −1 ).…”
Section: Leaf Traits and Tree Growthmentioning
confidence: 99%
“…This suggests that the biochemical properties of the leaf can be affected by the water stress, as suggested by Tezara et al (1999). The low photosynthetic rates observed under low light intensity is in agreement with the results reported by Nascimento and Marenco (2013) for saplings grown at the forest understory under natural conditions. In Tabebuia rosea, a tropical tree, A max values were 8.94 and 3.96 µmol m -2 s -1 in sun and shade plants, respectively (Kitajima and Hogan 2003), which is within the range reported in this study.…”
Section: Gas Exchange Parameterssupporting
confidence: 89%
“…Vários estudos em florestas tropicais têm relatado diversos efeitos da luminosidade nos processos fisiológicos (DENSLOW et al, 1990;MARENCO, 2010;MARENCO, 2013). Entretanto, não se sabe como mudanças da luminosidade no sub-bosque da floresta podem influenciar nas concentrações de N e P foliar e na eficiência do uso do N e P foliar na Amazônia Central.…”
Section: Mendes Kr E Marenco Raunclassified
“…Os valores de irradiância no sub-bosque observados neste estudo são similares aos descritos em outros trabalhos (MOLION, 1987;MARENCO, 2013), que relataram que a luz no sub-bosque da floresta é inferior a 2% de irradiância registrada acima do dossel da floresta. Nas florestas tropicais úmidas, as baixas taxas de crescimento (diâmetro e altura) nas espécies de sub-bosque estão relacionadas à baixa luminosidade a que as árvores são expostas na fase juvenil.…”
Section: Condições Ambientais E Crescimento Das Arvoretasunclassified